Graphene oxide-chitosan nanocomposite based electrochemical DNA biosensor for detection of typhoid - Singh, Anu; Sinsinbar, Gaurav; Choudhary, Meenakshi; Kumar, Veeresh; Pasricha, Renu; Verma, H.N.; Singh, Surinder P.; Arora, Kavita (Sensors and actuators. B, Chemical, 2013)
Graphene oxide (GO)-Chitosan (CHI) nano-composite is employed for the development of DNA based electrochemical biosensor for diagnosis of typhoid. Biosensor has been prepared by covalent immobilization of Salmonella typhi specific 5′-amine labeled single stranded (ss) DNA probe on GO-CHI/ITO via glutaraldehyde. Differential pulse voltammetry (DPV) studies revealed good specificity and ability of ssDNA/GO-CHI/ITO biosensor to distinguish complementary, non-complementary and one base mismatch sequences. The ssDNA/GO-CHI/ITO biosensor showed detection range of 10fM to 50nM and LOD 10fM within 60s hybridization times for complementary sequence. Further, ssDNA/GO-CHI/ITO bioelectrode is able to detect complementary target present in serum samples with LOD of 100fM at 25°C. The excellent performance of biosensor is attributed to large surface-to-volume ratio and good electrochemical activity of graphene oxide, and good biocompatibility of chitosan, which enhances the DNA immobilization and facilitate electron transfer between DNA and electrode surface (ITO).